Design and development of autonomous guided vehicle (AGV) - Abdul Hafiz, Mohamad (2007)
The technologies running fast we ever imagined before. The implementation of computer chip can be seen anywhere in every parts of this world. Humans are looking for automatic system that will make their life easier. This paper describes a project of design and development of autonomous guided vehicle (AGV). An AGV is a vehicle that uses no operator to drive that often used in material transportation in an automated production line or in automatic storage and retrieval system. This AGV running through the electronic programmed to drive the material or parts product to the specific destination. Sometimes this vehicle programmed to move to follow the line on the floor. This project required the student to build a prototype of an AGV in smaller scale but have the basic function as the real AGV where this prototype of AGV are able to move to the specific workstations and waiting for the task to accomplished. This project requested to complete the process of technical study, design, analysis, parts machining, assembly as well as testing and refinement of an AGV in the two-semester course. The four-wheeled AGY is driven by a stepper motor, move and steered by a different rotation of the motor. This AGV controlled by PlC microcontroller and TJLN2803AG integrated circuit. Through this project, students are able to learn how to innovate the technological product through the small scopes of project.